CARACTERISATION ET PROVENANCE DES MATERIAUX UTILISES DANS LA CONSTRUCTION DE LA MOSAÃQUE ROMAINE DU DIEU OCEAN DU SITE ARCHEOLOGIQUE DE LIXUS (MAROC) - Bouzoubaa, N.; Dekayir, A. (European Scientific Journal, ESJ, 2013)
The petrographic and mineralogical characterization of the â€œdieu OcÃ©anâ€ roman mosaic tessellatum show that the rocks used in the decoration are represented mainly by different kind of sandstone for pink and red tesseraes, limestone and marble for white tesseraes and doleritic basalt for green ones. The knowledge of the petrographical characteristics of different rocks used in this mosaic allows the localization of the quarries which provided natural materials to the site. The comparison between tesseraes and geological terrains surrounding the archaeological site, show that, sandstone, limestone and basalt were provided by the neighboring geological formations. Conversely, marble seems to imported.